2013
DOI: 10.1093/occmed/kqt007
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported work-related musculoskeletal injuries and isometric handgrip strength

Abstract: In this study, weak handgrip did not predict increased risk of musculoskeletal injuries/accidents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…In another study of 187 male workers in the English automotive industry, the average peak handgrip strength was found in the age group of 40–44 years with 47kg grip strength [ 17 ]. Thus, the male population of the present study has an average peak handgrip strength that is 6 kg higher than the English car industry population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In another study of 187 male workers in the English automotive industry, the average peak handgrip strength was found in the age group of 40–44 years with 47kg grip strength [ 17 ]. Thus, the male population of the present study has an average peak handgrip strength that is 6 kg higher than the English car industry population.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the male population of the present study has an average peak handgrip strength that is 6 kg higher than the English car industry population. We can infer from the report of the author of the fourth study, that the situation of lower grip strength may be associated with the lack of calibration of the dynamometers used [ 17 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study confirmed the effects of physical and psychosocial factors on neck symptoms in men. Later, Menegon and Fischer [132] studied the factors associated Meanwhile, Grobler [138] studied whether the isometric force of gripping a tool is a predictor of the risk of musculoskeletal injuries among workers of the automobile industry. The conclusion was that less isometric force is not associated with a greater risk of injury.…”
Section: Automobile Manufacturing Industrymentioning
confidence: 99%
“…The age group of[35][36][37][38][39] in the men's group had the values of 1 SD and 2 SD, respectively, 42.7 kg and 34.6 kg. The lowest values of 1 SD and 2 SD found in the group of men are in the 45-57 age group with 38.8 kg and 29.9 kg, 1 and 2 SD respectively.…”
mentioning
confidence: 99%